2014
DOI: 10.1261/rna.048173.114
|View full text |Cite
|
Sign up to set email alerts
|

Functional importance of Ψ38 and Ψ39 in distinct tRNAs, amplified for tRNAGln(UUG) by unexpected temperature sensitivity of the s2U modification in yeast

Abstract: The numerous modifications of tRNA play central roles in controlling tRNA structure and translation. Modifications in and around the anticodon loop often have critical roles in decoding mRNA and in maintaining its reading frame. Residues U 38 and U 39 in the anticodon stem-loop are frequently modified to pseudouridine (Ψ) by members of the widely conserved TruA/Pus3 family of pseudouridylases. We investigate here the cause of the temperature sensitivity of pus3Δ mutants of the yeast Saccharomyces cerevisiae an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
90
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(96 citation statements)
references
References 73 publications
6
90
0
Order By: Relevance
“…It has recently become appreciated that tRNA modifications that could alter the tRNA structure are affected by growth conditions. The effect of stress was reported for tRNA thiolation (Kamenski et al 2007;Damon et al 2015;Han et al 2015), m 5 C methylation (Preston et al 2013), and other modifications (Alings et al 2015). It is worth noting that activities of at least two enzymes responsible for end processing, RNase P and RNase Z, depend not on substrate sequence but proper structure (Takaku et al 2004;Mondragón 2013).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It has recently become appreciated that tRNA modifications that could alter the tRNA structure are affected by growth conditions. The effect of stress was reported for tRNA thiolation (Kamenski et al 2007;Damon et al 2015;Han et al 2015), m 5 C methylation (Preston et al 2013), and other modifications (Alings et al 2015). It is worth noting that activities of at least two enzymes responsible for end processing, RNase P and RNase Z, depend not on substrate sequence but proper structure (Takaku et al 2004;Mondragón 2013).…”
Section: Discussionmentioning
confidence: 92%
“…It has recently become appreciated that tRNA modifications are affected by stress (Chan et al 2010(Chan et al , 2012Preston et al 2013;Alings et al 2015;Damon et al 2015;Han et al 2015), but there are no reports regarding whether there is regulation of the activities responsible of pre-tRNA end-maturation. Here we investigated early steps of tRNA maturation for yeast grown at different temperatures (23°C-39°C) and in media with different carbon sources (glucose and glycerol).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it is unknown whether aberrant tRNAs imported to the nucleus via the retrograde process are repaired by nuclear tRNA posttranscriptional enzymes and/or whether they are degraded via the exosome or the Rat1 nuclear RTD enzyme. Moreover, recent studies showed that the extent of particular tRNA modifications is altered by environmental stresses (15)(16)(17)75), and it will therefore be interesting to learn how the resulting hypomodified tRNAs generated under such conditions escape the RTD quality control pathway. Finally, it is quite possible that an additional quality control mechanism(s) for tRNA production, subcellular distribution, and tRNA roles in protein synthesis has yet to be discovered.…”
Section: Perspectivesmentioning
confidence: 99%
“…There are 25 different nucleoside modifications reported for yeast tRNAs, and the average yeast tRNA contains ϳ11 to ϳ13 modified nucleosides (14). While some particular modified nucleosides serve important roles in accurate decoding, maintenance of reading frames, tRNA identity, responses to environmental stresses, and/or appropriate tRNA tertiary structures (14)(15)(16)(17)(18), the functions of other modifications remain unknown (14).…”
mentioning
confidence: 99%
“…However, in the last few years, it has become evident that the epitranscriptomic layer is not only dynamic and reversible (Jia et al 2011;Zheng et al 2013;Wang and He 2014;Liu et al 2016)-catalyzed by RNA modification "erasers" (Meyer and Jaffrey 2017)-but also that the activity of RNA modifications can be regulated by a wide variety of factors, including environmental conditions (Chan et al 2010;Dedon and Begley 2014;Alings et al 2015;Han et al 2015).…”
Section: Introductionmentioning
confidence: 99%